ANALISIS STRUKTUR KRISTAL LIMBAH MAGNET PERMANEN BERBASIS BESI OKSIDA - Cynthia Sagita; Mutia Delina; Erfan Handoko (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Has performed the initial characterization of BaFe12O19 wasted magnet (Barium Hexaferrite). Characterization has done by analyzing the crystal structure using X-Ray Difraction (XRD). The analysis showed that the sample is a single phase, namely BaFe12O19. Samples with a hexagonal crystal structure (space group P63 / mmc), lattice parameters a = b = 5.892 Å, c = 23.183 Å with and . Samples also have the atomic density of 5.32 and the unit cell volume 693.608 with a crystal size of 632.7 Å. The results showed BaFe12O19 wasted can be reused as a new magnet material. Key word: Barium Hexaferrite, magnet wasted, crystal structure and XRD.